Reduction of GHG emissions from ships: Evaluation of inter-company R&D cooperation models in the case of Hapag-Lloyd - Carsten Willer; Dirk Max Johns (Journal of Shipping and Trade (JST), 2021)
Decarbonization provides a crucial challenge for the maritime industry, resulting in growing concerns about how to achieve the initial IMO strategy on reduction of GHG-emissions from ships. In this context, R&D cooperation has become an important domain for industrial practice, constituting a preeminent strategic framework and vital factor for actively shaping the industry's development towards a sustainable future. Leading global liner-shipping companies emphasize the importance of R&D to surmount disruptive challenges. However, based on the variety of R&D cooperation models, it remains to be investigated how such collaborations should be configured. This paper seeks to address practical collaboration concepts by defining holistic requirements from a corporate perspective, which are subsequently matched with a portfolio of external stakeholders and cooperation configurations. For this process, a mixed-methods research design has been adopted, sourcing the required information from expert interviews with the primary stakeholder groups and culminating in the construction of two multi-criteria decision-making models to draw dynamic inferences.
Keywords: 650; Decarbonization; Liner shipping; R&D; Research cooperation; Sustainability